DESIGN OF PASAMAN CULTURE CENTER USING MINANGKABAU SYMBOLISM ARCHITECTURE APPROACH - Purnama Sakhrial Pradini (Universitas Pendidikan Indonesia, 2023)
Pasaman is one of the districts in the province of West Sumatra, Indonesia. The district capital is located in Lubuk sikaping, which is dominated by the Minangkabau ethnic group. Minangkabau is one of the tribes that is famous for its culture, language, special food, traditional houses, and various branches of art. However, over time, this art has begun to be abandoned. The entry of foreign culture is one of the factors that affect the decline in public interest in Pasaman Regency towards Minangkabau culture.In Pasaman itself there are still a small group of cultural circles who are still trying to preserve Minangkabau culture which the Pasaman local government is currently paying attention to, such as holding inter-nagari festivals. From this it can be seen that there are still people who care about Minangkabau culture in Pasaman, to preserve this culture it is necessary to have a Pasaman culture center as a forum that is able to regenerate public interest in Minangkabau culture, a gathering place for culturalists and art connoisseurs to continue to preserve culture. The Minangkabau architectural concept approach aims to give the nuances of Minangkabau customs, strengthen the image as a means of preservation and promotion of art and culture and its unique form will attract visitors to come and show the regional context through symbols as a characteristic of Minangkabau in Pasaman.